2020
DOI: 10.1108/omj-12-2018-0654
|View full text |Cite
|
Sign up to set email alerts
|

Do you pass it on? An examination of the consequences of perceived cyber incivility

Abstract: Purpose The emerging literature on computer-mediated communication at the study lacks depth in terms of elucidating the consequences of the effects of incivility on employees. This study aims to compare face-to-face incivility with incivility encountered via e-mail on both task performance and performance evaluation. Design/methodology/approach Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 49 publications
0
13
0
Order By: Relevance
“…While studies of each type of incivility independently have indicated both to Daily Effects of Incivility via Discrete Emotions 16 cause important impairments to employees (e.g., Zhou et al, 2015), emotions have only been studied as antecedents of cyber mistreatment (e.g., Vranjes et al, 2018), meaning that the potential for emotions to explain the detrimental effects of cyber incivility was unknown. More generally, our understanding of their relative effects has been hampered by the fact that the few previous studies that include both types of incivility suffer from methodological issues that limit the confidence of conclusions in application to day-to-day workplace incivility (e.g., use of student samples: McCarthy et al, 2020;Scisco et al, 2019; reliance on retrospective reports: Heischman et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While studies of each type of incivility independently have indicated both to Daily Effects of Incivility via Discrete Emotions 16 cause important impairments to employees (e.g., Zhou et al, 2015), emotions have only been studied as antecedents of cyber mistreatment (e.g., Vranjes et al, 2018), meaning that the potential for emotions to explain the detrimental effects of cyber incivility was unknown. More generally, our understanding of their relative effects has been hampered by the fact that the few previous studies that include both types of incivility suffer from methodological issues that limit the confidence of conclusions in application to day-to-day workplace incivility (e.g., use of student samples: McCarthy et al, 2020;Scisco et al, 2019; reliance on retrospective reports: Heischman et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, very few studies of the effects of incivility consider both face-to-face and cyber incivility. Those that do have relied on student participants(McCarthy, Pearce, Morton, & Lyon, 2020;Scisco, Giumetti, Bodinger, Randall, & Shemanskis, 2019), or have applied retrospective survey designs rather than studying daily effects(Heischman, Nagy, & Settler, 2019), and do not consider mediating variables, such as emotions. This prior research also reports conflicting patterns of findings.…”
mentioning
confidence: 99%
“…Online communication has become more prominent in universities and clinical settings [ 11 , 12 , 16 , 34 , 49 , 50 ], due to its advantages of flexibility of location and time [ 10 , 51 ], and its use is especially important, given the social distancing measures brought about by the COVID-19 pandemic [ 16 ]. Cyberincivility can have a profound negative psychosocial impact on users and their community [ 52 , 53 ], resulting in emotional distress (e.g., cynicism, fear, lowered self-confidence, and burnout), social isolation, distrust and avoidance, and turnover intentions [ 34 , 54 , 55 ]. The creation and maintenance of a safe, supportive, and civil learning environment is important for both educators and their students [ 56 , 57 ].…”
Section: Discussionmentioning
confidence: 99%
“…As technology-assisted work processes become increasingly common, it is critical to consider modality of work in future research on workplace mistreatment (Barber & Santuzzi, 2015). One direction of research is to more systematically examine the similarities and differences between in-person and online workplace mistreatment (e.g., cyber incivility, cyberbullying); indeed, some recent research has begun to do so (e.g., Heischman et al, 2019;McCarthy et al, 2020). Another promising direction is to explore more innovative ways of investigating the perpetrator's and witness's perspectives with workplace mistreatment in field research, through utilizing technology-assisted research methods (e.g., to code mistreatment behaviors displayed in Zoom video recordings of team meetings).…”
Section: Considering the Implications Of Remote Workmentioning
confidence: 99%